Myosin dynamics during relaxation in mouse soleus muscle and modulation by 2′‐deoxy‐ATP. (9th September 2020) - Ma, Weikang; Childers, Matthew; Murray, Jason; Moussavi‐Harami, Farid; Gong, Henry; Weiss, Robert; Daggett, Valerie; Irving, Thomas; Regnier, Michael
Abstract : Key points: Skeletal muscle relaxation has been primarily studied by assessing the kinetics of force decay. Little is known about the resultant dynamics of structural changes in myosin heads during relaxation. The naturally occurring nucleotide 2‐deoxy‐ATP (dATP) is a myosin activator that enhances cross‐bridge binding and kinetics. X‐ray diffraction data indicate that with elevated dATP, myosin heads were extended closer to actin in relaxed muscle and myosin heads return to an ordered, resting state after contraction more quickly. Molecular dynamics simulations of post‐powerstroke myosin suggest that dATP induces structural changes in myosin heads that increase the surface area of the actin‐binding regions promoting myosin interaction with actin, which could explain the observed delays in the onset of relaxation. This study of the dATP‐induced changes in myosin may be instructive for determining the structural changes desired for other potential myosin‐targeted molecular compounds to treat muscle diseases. Abstract: Here we used time‐resolved small‐angle X‐ray diffraction coupled with force measurements to study the structural changes in FVB mouse skeletal muscle sarcomeres during relaxation after tetanus contraction. To estimate the rate of myosin deactivation, we followed the rate of the intensity recovery of the first‐order myosin layer line (MLL1) and restoration of the resting spacing of the third and sixth order of meridional reflection (SM3 and SM6 ) following tetanic contraction. A transgenic mouse model with elevated skeletal muscle 2‐deoxy‐ATP (dATP) was used to study how myosin activators may affect soleus muscle relaxation. X‐ray diffraction evidence indicates that with elevated dATP, myosin heads were extended closer to actin in resting muscle. Following contraction, there is a slight but significant delay in the decay of force relative to WT muscle while the return of myosin heads to an ordered resting state was initially slower, then became more rapid than in WT muscle. Molecular dynamics simulations of post‐powerstroke myosin suggest that dATP induces structural changes in myosin that increase the surface area of the actin‐binding regions, promoting myosin interaction with actin. With dATP, myosin heads may remain in an activated state near the thin filaments following relaxation, accounting for the delay in force decay and the initial delay in recovery of resting head configuration, and this could facilitate subsequent contractions. Key points: Skeletal muscle relaxation has been primarily studied by assessing the kinetics of force decay. Little is known about the resultant dynamics of structural changes in myosin heads during relaxation. The naturally occurring nucleotide 2‐deoxy‐ATP (dATP) is a myosin activator that enhances cross‐bridge binding and kinetics. X‐ray diffraction data indicate that with elevated dATP, myosin heads were extended closer to actin in relaxed muscle and myosin heads return to an ordered, resting state after contraction more quickly. Molecular dynamics simulations of post‐powerstroke myosin suggest that dATP induces structural changes in myosin heads that increase the surface area of the actin‐binding regions promoting myosin interaction with actin, which could explain the observed delays in the onset of relaxation. This study of the dATP‐induced changes in myosin may be instructive for determining the structural changes desired for other potential myosin‐targeted molecular compounds to treat muscle diseases.